2021
DOI: 10.1016/j.jhep.2021.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of current liver donor allocation systems and the impact of newer indications for liver transplantation

Abstract: Liver transplantation represents a life-saving treatment for patients with decompensated cirrhosis, a severe condition associated with a high risk of waiting list mortality. When decompensation occurs rapidly in the presence of extrahepatic organ failures, the condition is called acute-on-chronic liver failure, which is associated with an even higher risk of death, though liver transplantation can also markedly improve survival in affected patients. However, there are still gaps in our understanding of how to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 101 publications
0
33
0
Order By: Relevance
“…This could lead to a more personalized approach regarding management of wait-list priority in ACLF and would ultimately improve patient's survival and LT outcomes [58].…”
Section: Wait-list Priority In Patients With Aclf Awaiting Lt: Beyond Meld-based Allocationmentioning
confidence: 99%
See 3 more Smart Citations
“…This could lead to a more personalized approach regarding management of wait-list priority in ACLF and would ultimately improve patient's survival and LT outcomes [58].…”
Section: Wait-list Priority In Patients With Aclf Awaiting Lt: Beyond Meld-based Allocationmentioning
confidence: 99%
“…To this end, new methods to improve assessment of LT eligibility in these patients are eagerly awaited, that is to evaluate whether an individual patient has become "too sick to be transplanted" [58,67]. The fact that no patient with ACLF and severe respiratory failure in the CANONIC trial underwent LT indicated that this condition was considered an absolute contraindication for LT in ACLF [49].…”
Section: Benefit Of Liver Transplantation In Patients With Alcf Gradementioning
confidence: 99%
See 2 more Smart Citations
“…The first of these is devoted to intensive care management of these patients with extremely high attendant risk of death 12 and the second to the issues surrounding liver transplantation of patients with ACLF and multiorgan failure. 13 This is particularly challenging because of the risk of potential futility and the lack of priority for patients at risk of imminent death, as current allocation systems fail to identify these high-risk patients.…”
mentioning
confidence: 99%